Pendapatan Nelayan di Kelurahan Kabola (Pantai Maimol) Perbulan Serta Faktor Yang Menghambat Aktifitas Nelayan - Gaudensius S. Yenifana; Melki I. Puling Tang; Jon A. Lalang Yame; Fidayanti Leki; Hana L. Atmalai; Herlina Karma; Adriana E. Bana; Astri R. Mau Sally (Jurnal Kajian dan Penelitian Umum, 2023)
Fishermen are a part of Indonesian society which is synonymous with the people who live in coastal ares by managing the potential of fishery resources. Fishermen are also people whose livelihood is catching fish. Many fishing communities in Indonesia catch fish using the help of traditional boats with simple tools to get fish without destroying natural ecosystems. These resources include animals, plants, and land that can be used directly or cultivated. So far, fishermen have made a real contribution to the development of fisheries and marine affairs as well the economi development of ommunities in the coastal areas and kabola sub-districts. The income of traditional firshmen in the kabola sub-district, kabola sub-district is based on the data we obtained on june 15 2023.The research model used is the exponential model. The type of data used is primary data. Primary data is data taken through observation, interviews and documentation. While the information in this study is a traditional fishing community. The results showed that the study of traditional society was Maimol beach, Kabola sub-district, Kabola sub-district, Alor district. Among others: 1). Completeness of traditional fishing equipment using simple equipment such as: small nets, canoes or boats and, fishing rods. 2). The strategy of traditional fishermen when fishing is by using a net, the net is lowered when it is in the middle of the ocean and then waited for about one or two hours, after which the net is pulled into the boat. in a day traditional fishermen need about 5 to 7 hours to get satisfactory results. 3). The income of traditional fishermen on the Maimol beach affects natural conditions. If natural conditions are good and supportive, the fishermen's income is very satisfying and if natural conditions are not good, then activities at sea are not carried out. Fishermen's income depends on natural conditions, a minimum of IDR 1,000,000 and a maximum RP. 3,000,000 and that too if the natural conditions are very good.